The Multifaceted Roles of the BCL-2 Family Member BOK - Naim, Samara; Kaufmann, Thomas (Frontiers in Cell and Developmental Biology, 2020)
BCL-2–related ovarian killer (BOK) is—despite its identification over 20 years ago—an incompletely understood member of the BCL-2 family. BCL-2 family proteins are best known for their critical role in the regulation of mitochondrial outer membrane permeabilization during the intrinsic apoptotic pathway. Based on sequence and structural similarities to BAX and BAK, BOK is grouped with these “killers” within the effector subgroup of the family. However, the mechanism of how exactly BOK exerts apoptosis is not clear and controversially discussed. Furthermore, and in accordance with reports on several other BCL-2 family members, BOK seems to be involved in the regulation of a variety of other, “apoptosis-independent” cellular functions, including the unfolded protein response, cellular proliferation, metabolism, and autophagy. Of note, compared with other proapoptotic BCL-2 family members, BOK levels are often reduced in cancer by various means, and there is increasing evidence for BOK modulating tumorigenesis. In this review, we summarize and discuss apoptotic- and non–apoptotic-related functions of BOK, its regulation as well as its physiological and pathophysiological roles.